2008
DOI: 10.1089/fpd.2008.0088
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Products Decrease Growth of E. coli O157:H7 and Salmonella Typhimurium in Pure Culture and in Fermentation with Mixed Ruminal Microorganisms In Vitro

Abstract: Orange peel and orange pulp are by-products that are included in feedlot and dairy cattle diets because of their low cost and high nutritional quality. The antimicrobial activity of citrus oils has been reported previously. The present study was carried out to determine whether these citrus by-products exert antimicrobial effects on Escherichia coli O157:H7 and Salmonella Typhimurium populations that are found in cattle gastrointestinal tracts. The growth of pure cultures (n = 3) of E. coli O157:H7 and Salmone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 33 publications
1
34
0
1
Order By: Relevance
“…However, in their studies Martin-Peláez et al (25,26) used very high numbers of Salmonella cells (Ͼlog 7.0 CFU), which would not naturally occur during a normal Salmonella infection. Callaway et al (7), using an in vitro simulation technique for ruminal fermentation, found that pectin could significantly reduce the prevalence of Salmonella. This was partially confirmed by our results, but only the relative proportion of Salmonella was reduced with pectin, as was also the case with the hull-less barley cultivars CDC McGwire, CDC Fibar, SH99250, and SB94893.…”
Section: Vol 75 2009 Cereal Carbohydrates and Intestinal Microbial mentioning
confidence: 99%
“…However, in their studies Martin-Peláez et al (25,26) used very high numbers of Salmonella cells (Ͼlog 7.0 CFU), which would not naturally occur during a normal Salmonella infection. Callaway et al (7), using an in vitro simulation technique for ruminal fermentation, found that pectin could significantly reduce the prevalence of Salmonella. This was partially confirmed by our results, but only the relative proportion of Salmonella was reduced with pectin, as was also the case with the hull-less barley cultivars CDC McGwire, CDC Fibar, SH99250, and SB94893.…”
Section: Vol 75 2009 Cereal Carbohydrates and Intestinal Microbial mentioning
confidence: 99%
“…This is potentially due to the diffusion properties of CBP across the cell envelope of E. coli . Others studies indicate that CBPs decrease E. coli O157:H7 populations from 24 h to 72 h [6, 16]. This study was only conducted for 6 h; an increased duration of the study could have been more beneficial to observe the effects of CBP on the various serotypes.…”
Section: Resultsmentioning
confidence: 98%
“…These results are in accordance with previous studies that have suggested a decrease in O157:H7 populations using other varieties of CBP. A study conducted by Callaway et al supplemented mixed ruminal microorganism fluid media with 0%, 0.5%, 1%, and 2% dried orange pulp and E. coli O157:H7 populations decreased according to increasing concentrations [6]. Reductions in E. coli O157:H7 populations have also been observed when sheep rations were supplemented with 5% or 10% orange peel [16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our hypothesis, based on the reported beneficial effects of citrus by-products on Escherichia coli 0157:H7 and Salmo nella Typhimurium in sheep and the antimicrobial properties of DL (2,7), was that we could reduce the concentration of Salmonella with the administration of DL and MOL. Unfortunately, we did not observe any beneficial effects of the citrus products under these experimental conditions.…”
Section: Discussionmentioning
confidence: 99%